تقييم أداء خوارزمية التوقيع الرقمي MQQ-SIG في شبكات الحساسات اللاسلكية الداعمة للوسائط المتعددة - معلا, بشرى; اسكندر, خديجة (Latakia University Journal -Engineering Sciences Series, 2018)
Wireless multimedia sensor network (WMSN) consists of large number of small size, low power, limited sources sensor nodes, which are deployed in tested field. These nodes have the ability to sense, to process, to store and to send multimedia data from the environment in real time. A security issue in WMSNs is one of important issues that should be study, because of the special nature of this network, and the importance of inquest basic security requirements of sending information in the network. Using digital signature is very effective way to verify source node`s identity, and it is considered as an important way to detect "Man In Middle" attack, and to achieve data integrity and privacy. MQQ algorithm which is recently proposed is one of public key cryptography (PKC) algorithms. This algorithm provides good performance as other PKC algorithms such as ECC and RSA. In addition, the implementation of digital signature based on MQQ algorithm -which is called MQQ-SIG- has very good advantages when applied to other networks. In this paper, we present an analyzing study of implementation MQQ-SIG in WMSNs. To achieve our goal, we used real images which are taken by multimedia wireless sensor nodes. We studied important parameters such as size of generated keys, execution time and space occupied in flash memory of multimedia wireless sensor nodes. Results showed that MQQ-SIG has good performance, as well as the short execution time for generating digital signature, and the execution time of signing and verification operations as similar as that of RSA algorithm. Results also showed the importance of taking into account a large size of public key of MQQ algorithm when implementation it in WMSNs. تتكون شبكة الحساسات اللاسلكية الداعمة للوسائط المتعددة (WMSN) من عدد كبير من العقد الحساسة صغيرة الحجم، منخفضة الطاقة، ومحدودة المصادر، يتم نشرها في حقل الاختبار. تمتلك هذه العقد القدرة على تحسس معطيات الوسائط المتعددة من البيئة المحيطة، وتخزينها، ومعالجتها وإرسالها في الزمن الحقيقي. تُعدّ قضية الأمن في هذه الشبكات إحدى القضايا المهمّة للدراسة، وذلك نظراً لطبيعتها الخاصّة، إضافة إلى أهمية تحقيق متطلبات الأمن الأساسية للمعلومات المُرسَلة عبر الشبكة. يُعدّ استخدام التوقيع الرقمي من أهم الأساليب المُتّبعة للتحقق من هوية العقدة المصدر، ومن أهم الطرائق المستخدمة للحد من هجوم "رجل في المنتصف" وبالنتيجة الحفاظ على خصوصية وتكاملية معطيات الشبكة. إن خوارزمية MQQ التي اقترحت حديثاً، هي إحدى خوارزميات المفتاح العام PKC. حققت هذه الخوارزمية أداءً جيّداً مقارنةً مع نظيراتها من خوارزميات المفتاح العام الأخرى مثل خوارزميتي RSA و ECC. إضافة إلى ذلك، إن تنفيذ التوقيع الرقمي اعتماداً على خوارزمية MQQ - والذي يُدعى بـ MQQ-SIG - حقق مزايا جيّدة عند تطبيقه على الشبكات الأخرى. نقدّم في هذا البحث دراسة تحليلية لتطبيق MQQ-SIG في شبكات الحساسات اللاسلكية الداعمة للوسائط المتعددة. لتحقيق هدفنا استخدمنا صوراً حقيقية ملتقطة من قبل عقدة حساس لاسلكي داعم للوسائط المتعددة، وتم دراسة بعض البارامترات الهامّة التي تقيم أداء هذه الخوارزمية مثل حجم المفاتيح المولدة وزمن التنفيذ والحيز المحجوز من ذاكرة الحساس. أظهرت النتائج أن MQQ-SIG قدم أداءً جيداً، فضلاً عن الزمن القصير لتوليد التوقيع الرقمي، وزمن تنفيذ عملية التوقيع والتحقق المماثل لما هو في خوارزمية RSA. كما بينت النتائج أيضاَ ضرورة أخذ الحجم الكبير للمفتاح العام بالحسبان عند تطبيقها في شبكات الحساسات اللاسلكية الداعمة للوسائط المتعددة.